Addressing Female Iron-Deficiency Anaemia in India: Is Vegetarianism the Major Obstacle?. (2012) - Rammohan, Anu; Awofeso, Niyi; Robitaille, Marie-Claire
Abstract : Objectives . We examined the influence of vegetarian diet on the risk of developing anaemia among Indian women and suggest initiatives for addressing diet-related iron-deficiency anaemia. Methods . We analysed data on diet, social class, and haemoglobin levels from the nationally representative Indian National Family and Health Survey 2005/06 for a sample of 81, 301 women aged 15–49 years using logistic regression models. Results . After controlling for individual-level factors and household level socioeconomic characteristics, daily consumption of meat, fish, and eggs was associated with lower odds of being moderately or severely anaemic. Our analysis also revealed that economic characteristics such as being from higher wealth quintiles, being in paid employment, and rural residence reduced the odds of having iron-deficiency anaemia among Indian women. Discussion . As a large proportion of Indians subsist on iron-poor vegetarian diets for religious, economic, and cultural reasons, large-scale iron supplementation and fortification of commonly consumed vegetarian foodstuffs constitute a feasible, culturally appropriate, and cost-effective strategy for addressing this major public health problem. Consumption of cheap iron-rich foodstuffs should be promoted. Effective poverty alleviation and hookworm prevention programs are also important. Large-scale cohort and intervention studies are urgently required to further define the influence of vegetarianism on iron deficiency anaemia in India.